New species of Glossosomatidae from Bolivia with new records from Bolivia and northwestern Argentina (Trichoptera: Glossosomatidae) - Rueda Martin, Paola Alejandra (2008)
Seven new species of Glossosomatidae are described from Bolivia. The seven new Bolivian species are: Mexitrichia collegarum n. sp., M. eduardoi n. sp., M. marini n. sp, M. usseglioi n. sp, Protoptila alumnorum n. sp, P. goitiai n. sp and P. myriamae n. sp. 18 species are recorded at the moment from Bolivia and northwestern Argentina: Merionoptila wigodzinskyi, Mexitrichia albolineata, M. bolivica, M. pocita, M. punensis, M. simla, M. argentinica, M. paraenchrysa, M. wygodzinskii, Protoptila dubitans, P. misionensis and the seven new species. A list of species of Glossosomatidae from Bolivia and northwestern Argentina is provided with new distributional records.